EXPLORING LEADERSHIP STYLES AND EMPLOYEE WELL-BEING: A CROSS-CULTURAL PERSPECTIVE IN MULTINATIONAL CORPORATIONS - Puspita Puji Rahayu; Ren Suzuki; Sota Yomamoto (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
In multinational corporations (MNCs), leadership styles play a pivotal role in shaping employee well-being, which in turn influences organizational performance. However, the impact of leadership on employee well-being varies significantly across different cultural contexts. This study explores how various leadership styles—transformational, transactional, and laissez-faire—affect employee well-being within MNCs operating in diverse cultural settings. The primary objective is to examine the relationship between leadership styles and employee well-being across four regions: North America, Europe, Asia, and the Middle East. A mixed-methods approach was employed, combining quantitative surveys (300 employees) and qualitative interviews (30 managers) to gather comprehensive data on leadership styles and employee well-being. The results indicate that transformational leadership is positively correlated with high employee well-being, particularly in individualistic cultures, while transactional leadership shows a weaker association with well-being in more collectivist cultures. The study also highlights significant regional differences in leadership perceptions and their impact on employee engagement and job satisfaction. This research underscores the importance of culturally adaptive leadership practices and provides practical implications for MNCs seeking to optimize employee well-being across diverse workforces.